Ecologist's approach to sustainable development. - REES, Colin (1993)
Stresses the preservation of the integrity of ecological subsystems as critical for the overall stability of the global ecosystem. Concludes that ecologists will influence policy only if they can demonstrate that sound ecological policies will promote sustainable economic development.